Corruption and Money Laundering Perspective of Criminal Law and Criminology - Maria Silvya Elisabeth Wangga; Aditya Wirawan; R. Bondan Agung Kardono (Publindo Akademika, 2022)
Criminal acts of corruption and money laundering are increasingly complex, neat and sophisticated, carried out by educated people with the positions of Members of the DPR, DPRD, Heads of Institutions/Ministries, Governors, Mayors/Regents and Deputy Echelon I/II, judges, and private parties with various ages and come from different regions. The mode is through procuring goods and services, licensing, bribery, levies, budget abuse and money laundering. Social factors that encourage perpetrators to commit crimes can be explained through social exchange theory which shows that there is an abuse of office, doing something contrary to obligations and bribing bribes that lead to crimes in the field of corruption and money laundering. This fact is very close to the change in value orientation in the social life of everyone, whether it is law enforcement officers, state officials, or community members.